O poder de polícia e a atividade sancionatória nos mercados financeiro e de capitais - Verzola, Antonio Carlos (2008)
This dissertation aims at examining the exercise of the Police Power by the Public Administration, taking the discretionary competence as a reference, by confronting such Police Power with the legally posed limits and the qualification that is invested to it by the administrative doctrine. That is so because, even though the Public Administration is acknowledged to be liable of using a certain margin of subjectivism in its manifestations, where the law grants it, through the use of convenience and opportunity criteria, it should never be placed at the edge of the legal system. Thence, its actions will be always subjected to the rules and principles that guide the administrative activity and establish the State limits regarding the citizen. After generically analyzing the correlate issues to the main point, the work particularizes the approach, by centering it in the Police Power that is intrinsic to the Brazilian Central Bank and the Federal Securities Commission, in the leading of sanctioning administrative proceedings, either established by one or another, out of those public entities, in their respective legal environment, as well as in the enactment of special systems by the foremost, facing institutions under its supervision. At a first instance, the study offers a theoretical view in relation to the subject, and then it brings an illustrative panel of the practical aspect of those entities regulating activity in the financial and capital markets. Accordingly. grounded on the Brazilian Law and on the national and foreign doctrines, the study can lead to the conclusion that there is no wavelength on what the legal actions on the subject should determine and on what the respective doctrine and the attitude taken by public administrators should rule, when acting under alleged exercise of discretionary competence. In other occasions of such situations, the Public Administration understands it has a broader power than the legally entitled power and uses subjective assessments that are not comprised by legal authorization. Such an absence of correspondence or lack of synchronicity becomes evident in connection with the general principles, either those that are inherent to the generically considered exercise of Law, or even those other ones that are pertaining to the juridical and administrative system